Paul and the rhetoric of reversal: kerygmatic rhetoric in the arrangement of 1 Corinthians - Malcolm, Matthew R. (2011)
I argue that 1 Corinthians is a unified composition that exhibits kerygmatic rhetoric. That is, Jewish and Greco-Roman resources are brought into the service of an overall arrangement that is creatively suggested by Paul's kerygma of the Messiah who died, rose, and awaits cosmic manifestation. In particular, I demonstrate that the Jewish motif of dual reversal, whereby boastful rulers are destined for destruction while righteous sufferers are destined for vindication, serves as an influential conceptual motif in the formulation of Christian kerygma, and as such may be seen as an interpretative framework and rhetorical resource available to Paul.